Karakteristik Lokasi Usaha Kerajinan Monel di Desa Kriyan, Kecamatan Kalinyamatan, Kabupaten Jepara - Solekhah, Nabiila Nuri; Tyas, Wido Prananing (Jurusan Perencanaan Wilayah dan Kota, 2023)
Kriyan Village is one of the villages that have regional potential in the form of monel crafts. Monel crafts are Home-based Enterprises (HBE) that have been established since the 1970s and continue to grow today. Fans of monel craft accessories are quite broad because marketing distribution does not only occur in the country but has reached overseas. The number of monel artisans is currently also dominated by the elderly. This is a problem considering that the monel craft business has become the starting point for the development of business centers and is still the economic foundation for the people of Kriyan Village, which should be preserved. The study findings indicate that Kriyan Village has an important role in developing the household business category monel handicraft business in Kriyan Village because it can provide the needs of raw materials and labor. This finding is expected to describe the distribution pattern of the monel craft business and the location advantage factors that affect the existence of the monel craft business in Kriyan.